ASKP1240, a Fully Human Anti‐CD40 Monoclonal Antibody, Prolongs Pancreatic Islet Allograft Survival in Nonhuman Primates. Issue 8 (10th July 2013) - Watanabe, M.; Yamashita, K.; Suzuki, T.; Kamachi, H.; Kuraya, D.; Koshizuka, Y.; Ogura, M.; Yoshida, T.; Aoyagi, T.; Fukumori, D.; Shimamura, T.; Okimura, K.; et al.
Abstract: A strategy for inhibiting CD40 has been considered as an alternative approach for immunosuppression because of undesirable effects of anti‐CD154 monoclonal antibodies (mAbs). Previously, we demonstrated that ASKP1240, which is a fully human anti‐CD40 mAb, significantly prolonged kidney and liver allograft survival in cynomolgus monkeys without causing thromboembolic complications. Herein, we evaluated the effect of ASKP1240 on pancreatic islet transplantation (PITx) in cynomolgus monkeys. Diabetes was induced by total pancreatectomy, and islet allografts were transplanted into the liver. Following PITx (8201–12 438 IEQ/kg), blood glucose levels normalized promptly in all animals. Control islet allografts were rejected within 9 days (n = 3), whereas ASKP1240 (10 mg/kg) given on postoperative days 0, 4, 7, 11 and 14 (induction treatment, n = 5) significantly prolonged graft survival time (GST) to >15, >23, 210, 250 and >608 days, respectively. When ASKP1240 (5 mg/kg) was administered weekly thereafter up to post‐PITx 6 months (maintenance treatment, n = 4), GST was markedly prolonged to >96, >115, 523 and >607 days. During the ASKP1240 treatment period, both anti‐donor cellular responses and development of anti‐donor antibodies were abolished, and no serious adverse events were noted. ASKP1240 appears to be a promising candidate for immunosuppression in clinical PITx. Abstract : The authors find that the blockade of CD40 by ASKP1240 suppresses cellular and humoral alloimmune responses, prolongs pancreatic islet allograft survival in nonhuman primates, and might be a promising approach for immunosuppression in clinical pancreatic islet transplantation.